Effects of Neonatal Deafness on Central Tonotopic Organization in Rats: an Electrophysiological Study - Woongsang Sunwoo; Yeeun Kim (Clinical and Experimental Otorhinolaryngology, 2026)
Objectives. Spatial mapping of sound frequencies along the auditory pathway is refined through sound-evoked activity during early development. However, how neonatal auditory deprivation alters this organization remains unclear. This study examined frequency-specific spatial representations in the inferior colliculus (IC) using targeted low-frequency (apical) and high-frequency (basal) cochlear stimulation, enabling direct evaluation of low-frequency pathway integrity after neonatal deafness.Methods. Sixteen Sprague-Dawley rats (8 normal-hearing [NH] and 8 neonatally deafened [ND]) were studied. Neonatal deafness was induced by daily kanamycin injections from postnatal days 4 to 17. At 8–10 weeks of age, all animals underwent unilateral cochlear implantation with bipolar electrode pairs positioned in apical and basal cochlear regions to activate low- and high-frequency pathways. Multiunit responses were recorded from the contralateral IC using a multichannel linear electrode array. Spatial tuning curves (STCs) based on cumulative discriminability were used to assess thresholds, spread of excitation, and tonotopic precision. Spiral ganglion neuron (SGN) density was quantified histologically.Results. Despite 48%–67% SGN loss across cochlear turns, electrically evoked auditory brainstem response thresholds and IC thresholds were comparable between groups, indicating preserved peripheral excitability. However, ND rats exhibited significantly broader STCs (P=0.002) and reduced dorsoventral separation of apical and basal best sites (1.18± 0.67 mm vs. 1.80±0.40 mm, P=0.039), reflecting degraded central tonotopic precision. The effects were most pronounced for apical (low-frequency) stimulation, consistent with the selective vulnerability of low-frequency pathways to early auditory deprivation.Conclusion. These findings provide direct physiological evidence that early auditory experience is critical for refining frequency-organized connectivity in the auditory midbrain. The preferential degradation of apical (low-frequency) spatial tuning offers translational insights for optimizing stimulation strategies in early-onset deafness.